PENGARUH CORPORATE SOCIAL RESPONSIBILITY PADA AGRESIVITAS PAJAK DAN MANAJEMEN LABA SEBAGAI PEMODERASI - Dita Braditya, Ida Bagus; Supadmi, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024DO - 10.24843/EEB.2024.v13.i04.p19, 2024)
Tax aggressiveness is an action that aims to reduce taxable profit through tax planning. The practice of tax aggressiveness by avoiding tax payments or reducing the tax burden paid will significantly takes benefit, so that the amount of cash enjoyed by the owners/shareholders in the company becomes greater. This study aims to determine by empirically testing the effect of the interaction between Corporate Social Responsibility and earnings management on tax aggressiveness. This research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019. Determination of the number of samples in this study using a purposive sampling technique. Based on the criteria in this study, the number of samples used in this study were 28 samples of companies with 84 observational data. Data were analyzed using Moderated Regression Analysis (MRA). The results of this study indicate that Corporate Social Responsibility has a negative and significant effect on tax aggressiveness and earnings management is a moderating variable that weakens the negative effect of corporate social responsibility on tax aggressiveness.